Energy and exergy performance of R290 as a substitute for R404A in freezers: experimental investigation - Akmal, Muhammad; Sumeru, Kasni; Tohir, Toto; Hikmat, Yudi Prana; Nuryati, Neneng; Sulaimon, Shodiya (Politeknik Negeri Lhokseumawe, 2025)
The refrigeration sector significantly contributes to global warming due to the high Global Warming Potential (GWP) of commonly used refrigerants. This study experimentally investigates the feasibility of using R290 as a low-GWP substitute for R404A in freezer applications. Although R290 and R404A have similar normal boiling points, their GWP values differ significantly (3 for R290 vs. 3922 for R404A), making R290 a more environmentally friendly alternative. Experiments were conducted on a freezer originally designed for R404A with a 1/3 HP compressor and a refrigerant charge of 170 g. After baseline testing with R404A, the system was retrofitted with R290, using an optimized charge of 62.9 g. The system's performance was analyzed over 120 minutes, with energy and exergy evaluations conducted at 60 minutes, when the cabin temperature stabilized. Results from energy analysis indicate that replacing R404A with R290 led to a 6.1% increase in cooling capacity, a 6.0% reduction in power consumption, and a 12.4% improvement in COP. Exergy analysis showed that total irreversibility decreased from 318.1 W (R404A) to 289.8 W (R290), with compressor irreversibility being the dominant factor (50.8% for R404A vs. 51.3% for R290). The findings confirm that R290 enhances system performance by reducing irreversibility and energy consumption. These results highlight R290 as an energy-efficient and environmentally friendly alternative to R404A, providing both operational cost savings and reduced environmental impact. However, to achieve optimal performance, compressor lubricant replacement is recommended when transitioning to R290.